Transdermal Oxandrolone: Ex Vivo Percutaneous Absorption Study - Polonini, Hudson; de Oliveira Ferreira, Anderson; Rezende Barbosa Raposo, Nádia; Antonio Fernandes Brandao, Marcos (Current Drug Delivery, 2017)
Background: Oxandrolone is a potent synthetic testosterone analogue that possesses strong anabolic property and weak androgenic activity. Apart of their clinical implicances, oral oxandrolone can potentially promote several adverse effects. It is known that the transdermal delivery of drugs may represent a means to avoid or minimize oral adverse effects Thus, the objective of this study was to evaluate the permeability of oxandrolone in human skin on a preliminary basis for possible future determination of the transdermal route as an alternative to oral treatments. Methods: We used a percutaneous absorption assay in Franz diffusion cells coupled with freshly excised human skin. The drug release kinetics were determined to predict the efficiency of this alternative route for the drug. Results: Nearly 236 μg (86.7%, in terms of applied dose) of the product was prevented to permeate due to the barrier function of the stratum corneum (SC); 21.6% reached the receptor medium (RM), and the remaining 4.3% were quantified within viable layers of the skin (in vivo, dermis is vascularized). The total amount of drug able to exert effect is the sum of the drug quantified within remained skin (RS) and RM: then, a total of 247.6 μg of oxandrolone (25.9% of the applied dose) would be able to permeate through a non damaged skin. The accuracy of the data is demonstrated by the calculated mass balance (average recovery = 112.6%). Conclusion: Transdermal oxandrolone could be a viable alternative for traditional oral form, once clinical studies are conducted to prove this hypothesis.
Keywords: oxandrolone